Answer:
a) The system is under-damped
b) The steady state response,
![x_(p) = (8 sin(5t))/(15)](https://img.qammunity.org/2021/formulas/physics/college/vvq4bsaj0myka6vqmfp9zw2hfrluaxaxuo.png)
c) The transient response,
![x_(h) = (ie^((-3-4i)t)(-1+e^(8it) )/(3)](https://img.qammunity.org/2021/formulas/physics/college/117bquh5ttf707l06v97y7j254fgv8co6q.png)
d) The total response,
![x(t) = (8 sin(5t))/(15) +(ie^((-3-4i)t)(-1+e^(8it) ) )/(3)](https://img.qammunity.org/2021/formulas/physics/college/q91r604guusm5chfwnnyls2cfx2fogp2h3.png)
x(t) was plotted on matlab
Step-by-step explanation:
a) The equation is :
............(1)
The general equation of a spring-mass-damper system is given by:
....................(2)
Comparing equation (1) with equation (2)
![w_(n) ^(2) = 100/4\\w_(n) = 52 \zeta w_(n) = 6\\2 * 5 * \zeta = 6\\\zeta = 0.6](https://img.qammunity.org/2021/formulas/physics/college/5pzeumt7jw1s75acd0uitbw4w5a5v07unb.png)
Since
, the system is under-damped
b) Take the inverse laplace transform of equation (1)
![(4s^(2) + 24s + 100) X(s) = (16s)/(s^(2) + 25 )](https://img.qammunity.org/2021/formulas/physics/college/uchqn61ti2tznwj03kw03vfxp43f8uk2lf.png)
![(4s^(2) + 24s + 100)(s^(2) + 25) X(s) = 16s\\X(s) = (16s)/((4s^(2) + 24s + 100)(s^(2) + 25))](https://img.qammunity.org/2021/formulas/physics/college/odfh4ywzm51thqc9e7p0lpzngvc393bdtr.png)
Taking the Inverse laplace transform of X(s)
![x(t) = (16 sin(5t))/(30) + 16 (ie^((-3-4i)t)(-1+e^(8it) )/(48)](https://img.qammunity.org/2021/formulas/physics/college/wjrltax3tlgdhp38o4nm2rre4lpkb1vd4n.png)
The steady state response is:
![x_(p) = (16 sin(5t))/(30)](https://img.qammunity.org/2021/formulas/physics/college/uar4hyjvowneq190mf6vd5ya048t3l2n6b.png)
c) The transient response is:
![x_(h) = (16ie^((-3-4i)t)(-1+e^(8it) ) )/(48)\\x_(h) = (ie^((-3-4i)t)(-1+e^(8it) )/(3)](https://img.qammunity.org/2021/formulas/physics/college/7prf99u7echbsxkidmao1yjgxuuxxpdsbl.png)
d) The total response:
![x(t) = x_(h) + x_(p) \\](https://img.qammunity.org/2021/formulas/physics/college/wng57gl9ktqqf4jua8w8prswst1c9i6ds9.png)
![x(t) = (8 sin(5t))/(15) +(ie^((-3-4i)t)(-1+e^(8it) ) )/(3)](https://img.qammunity.org/2021/formulas/physics/college/q91r604guusm5chfwnnyls2cfx2fogp2h3.png)